Penerapan Pendekatan Kooperatif Model STAD untuk Meningkatkan Kemampuan Menulis Berita Siswa Kelas V SDN 41 Mataram - Johariah, Hj. (Lembaga Yasin AlSys, 2022)
This research was motivated by a lack of writing skills, especially writing news for class V SDN 41 Mataram in the 2018/2019 academic year. Based on preliminary observations, information was obtained that the learning outcomes of fifth grade students in Indonesian, especially writing, were still very low. Based on these problems, the researcher chose to use a cooperative approach to the Student Teams Achievement Division (STAD) model to improve the ability to write news. This study uses Classroom Action Research. From the results of the evaluation of the first cycle, the score obtained was 34.78% completeness percentage. In cycle II, a completeness value of 91.31% was obtained. Teacher activity and student activity also increased. This can be seen in teacher activity in the first cycle, the average percentage is 71.5% and in the second cycle, the average percentage is 84.6%. Student activity in cycle I averaged 68.1% and in cycle II averaged 84.1%. So it can be concluded that there was an increase in the ability to write news with the application of the STAD model cooperative approach from cycle I to cycle II of 56.53% in Indonesian subjects with classical completeness of 91.31%. It is hoped that further research will be carried out on the application of the cooperative approach to the Student Teams Achievement Division (STAD) model in classroom settings or other schools.